COMPUTATIONAL ANALYSIS OF HOMEODOMAIN-LEUCINE ZIPPER (HD-ZIP) FAMILY OF TRANSCRIPTION FACTORS IN ARABIDOPSIS THALIANA - M. S. Javaid; U. A. Ashfaq; M. Ijaz; B. Naz; B. Saleem; A. Arshad; Mahmood-ur-Rahman (Journal of Animal and Plant Sciences, 2020)
Homeodomain-leucine Zipper (HD-Zip) proteins are a class of transcription factors having conserved homeodomain. Homeo box, conserved part of homeodomain consists of 56 residues and is involved in plant development. We retrieved protein sequences of all the 48 HD-Zip family members, performed genome-wide analysis, and grouped them into four subfamilies. A comprehensive genomic analysis including mapping of all the transcription factors on 5 chromosomes of Arabidopsis thaliana, multiple sequence alignment to find out the conserved domains, phylogenetic, and gene structure analysis by mapping introns and exons, promoter analysis by taking 1000bp upstream genomic sequence of all these transcription factors and motif analysis was performed in this study. The results helped us to understand the functional homology among HD-Zip transcription factors, comparison of the tree with motifs that further depends upon the number of exons and introns. This classification and analysis further categorized the transcription factors of 4 HD-Zip subfamilies into different classes and revealed a deep evolutionary relationship among them and thus helped to further explore their functioning.
Keywords: HD-Zip family; Arabidopsis thaliana; Homeo box; phylogenetic analysis; motif